The woman with no name : a novel - Blake, Audrey, active 2020 (Sourcebooks Landmark, 2024)
"1942.Though she survived the bomb that destroyed her home, Yvonne Rudellat's life is over. She's estranged from her husband, her daughter is busy with war work, and Yvonne--older, diminutive, overlooked--has lost all purpose. Until she's offered a chance to remake herself entirely... The war has taken a turn for the worse, and the men in charge are desperate. So, when Yvonne is recruited as Britain's first female sabotage agent, expectations are low. But her tenacity, ability to go unnoticed, and aptitude for explosives set her apart. Soon enough she arrives in occupied France with a new identity, ready to set the Nazi regime ablaze. But there are adversaries on all sides. As Yvonne becomes infamous as the nameless, unstoppable woman who burns the enemy at every turn, she realizes she may lose herself to the urgent needs of the cause..."--Page 4 of cover.